Interleukin-6 in Rheumatoid Arthritis - Pandolfi, Franco (Int J Mol Sci, 2020)
The role of interleukin (IL)-6 in health and disease has been under a lot of scrutiny in recent years, particularly during the recent COVID-19 pandemic. The inflammatory pathways in which IL-6 is involved are also partly responsible of the development and progression of rheumatoid arthritis (RA), opening interesting perspectives in terms of therapy. Anti-IL-6 drugs are being used with variable degrees of success in other diseases and are being tested in RA. Results have been encouraging, particularly when anti-IL-6 has been used with other drugs, such as metothrexate (MTX). In this review we discuss the main immunologic aspects that make anti-IL-6 a good candidate in RA, but despite the main therapeutic options available to target IL-6, no gold standard treatment has been established so far.